2021
DOI: 10.3390/recycling6040082
|View full text |Cite
|
Sign up to set email alerts
|

Best Available Technology for P-Recycling from Sewage Sludge—An Overview of Sewage Sludge Composting in Austria

Abstract: In order to close the phosphorus cycle in the long term, efficient recycling processes are necessary to ensure that this critical nutrient can be returned to arable land. Sewage sludge recycling is of particular importance due to the relatively high phosphorus content of sewage sludge. In this article, the current recycling paths of Austrian sewage sludge are highlighted, focusing on the advantages and limitations of sewage sludge composting. In addition to nutrient contents, pollutant loads were also analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
1
1
0
Order By: Relevance
“…According to Gorlach and Mazur (2002), the phosphorus content of cattle manure is 0.28%, which makes the compost obtained in this study richer in phosphorus. Studies conducted by other authors have also shown that sewage sludge compost can be a good source of phosphorus (Stürmer & Waltner, 2021). In addition, the potassium content is also similar to that obtained in a study conducted by Bożym et al (2014), where it was 1.24% and 1.21% for one-and two-year compost, respectively.…”
Section: Properties Of the Obtained Compostsupporting
confidence: 86%
See 1 more Smart Citation
“…According to Gorlach and Mazur (2002), the phosphorus content of cattle manure is 0.28%, which makes the compost obtained in this study richer in phosphorus. Studies conducted by other authors have also shown that sewage sludge compost can be a good source of phosphorus (Stürmer & Waltner, 2021). In addition, the potassium content is also similar to that obtained in a study conducted by Bożym et al (2014), where it was 1.24% and 1.21% for one-and two-year compost, respectively.…”
Section: Properties Of the Obtained Compostsupporting
confidence: 86%
“…However, to ensure the desired product quality, it is estimated that the share of sediment in the compost mass should not exceed approx. 30% by weight (Stürmer & Waltner, 2021). Therefore, composting sewage sludge is only possible with other substrates.…”
Section: Introductionmentioning
confidence: 99%